Assessing the Potential of Cultural Tourism Development in Kabale District - Simon, Otebwa (Kabale University, 2019)
A Research Report Submitted in Partial Fulfillment of the Requirement for the Award of a Degree of Bachelor of Tourism Management of Kabale University